1997
DOI: 10.1111/j.1558-5646.1997.tb03965.x
|View full text |Cite
|
Sign up to set email alerts
|

INCIPIENT SPECIATION BY SEXUAL ISOLATION INDROSOPHILA MELANOGASTER: VARIATION IN MATING PREFERENCE AND CORRELATION BETWEEN SEXES

Abstract: Genetic divergence for characters pertaining to reproductive isolation is of considerable interest in evolutionary biology. Since most studies concentrate on sibling species (for recent reviews, see Wu et al. 1996), we would like to know how much genetic variation exists between populations that are at an incipient stage of speciation. To answer this question, we have begun measuring variations in mating preference among natural isolates of Drosophila melanogaster, represented by the cosmopolitan and Zimbabwe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
146
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(165 citation statements)
references
References 28 publications
18
146
1
Order By: Relevance
“…A suggestion may be that the divergence in the transcription factors (TFs) or trans-acting components on chromosome II is less than that of TFs on chromosome III, because the Z and M races separated. Hollocher et al (11) and Ting et al (14) have reported similar chromosome-wide differences. Between the Z and M races, the contribution to behavioral differentiation is substantially larger for chromosome III than for chromosome II.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…A suggestion may be that the divergence in the transcription factors (TFs) or trans-acting components on chromosome II is less than that of TFs on chromosome III, because the Z and M races separated. Hollocher et al (11) and Ting et al (14) have reported similar chromosome-wide differences. Between the Z and M races, the contribution to behavioral differentiation is substantially larger for chromosome III than for chromosome II.…”
Section: Discussionsupporting
confidence: 55%
“…The Zimbabwe race of D. melanogaster vis-à-vis the cosmopolitan populations are thus well suited to such a purpose. Females from Z lines (for Zimbabwe) do not readily mate with males from M lines (for melanogaster of the cosmopolitan type), whereas the reciprocal crosses experience much weaker or no discrimination (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The former race occurs throughout the world, whereas the latter has been described from Zimbabwe, Zambia, and Botswana. In some parts of Africa, such as Zimbabwe, individuals of both races appear to be sympatric (Hollocher et al, 1997b;Fang et al, 2002;Takahashi and Ting, 2004). These races show marked but asymmetric sexual isolation: Zimbabwe-type females discriminate strongly against cosmopolitan males, whereas the reciprocal mating occurs readily (Wu et al, 1995;Hollocher et al, 1997a).…”
Section: Modalities Of Chemosensory Isolationmentioning
confidence: 99%
“…Subsequent studies revealed strong sexual isolation between these strains (Wu et al, 1995;Hollocher et al, 1997a, b) but little postzygotic isolation (Alipaz et al, 2005), indicating an early stage of speciation. Genetic analyses revealed that both male and female traits involved in assortative mating were most strongly influenced by chromosome 3 and least of all by the X chromosome (for example, Wu et al, 1995;Hollocher et al, 1997b;Ting et al, 2001;Michalak et al, 2007).…”
Section: Speciation and Sex-linked Genesmentioning
confidence: 99%